The Uncertainty of Oil: Balancing through the Temporalities and Affects of Depletion in Gabonfuture, decline, uncertainty, natural resources, Gabon - Fricke, Christine (Swiss Journal of Sociocultural Anthropology, 2017)
This paper argues that uncertainty is intricately entwined with temporalities and aff ects. Taking the uncertain future of oil in Gabon as my ethnographic example, I trace fi ve versions with which people contemplate depletion: a scenario, a vision / plan, a calculation, a dream, and a desire. I show how these versions not only diff er in their prognosis, but also conjure up diverse histories, temporalities and aff ects that, ultimately, entail fairly distinct forms of uncertainty.